From silence to sanction: comparative analysis of necrophilia laws in India and other countries - Hifajatali Sayyed; Jyotsana Singh (Cogent Social Sciences)
This research paper focuses into the legal liability of necrophilia across various jurisdictions, with a focus on India. Necrophilia, a deeply stigmatized and seldom-discussed crime, presents unique challenges for legislators and legal practitioners. In India, the legal framework addressing necrophilia is often ambiguous, leading to inconsistencies in prosecution and punishment. This study aims to illuminate the gaps in Indian law by comparing it with the legal approaches of other countries, including those with explicit statutes and stringent penalties. Through a detailed examination of case laws, statutory provisions, and legal commentaries, the research identifies the strengths and weaknesses of different legal systems in dealing with necrophilia. The comparative analysis seeks to provide a comprehensive understanding of how different cultural, social, and legal contexts influence the formulation and enforcement of laws against necrophilia. By highlighting best practices and potential pitfalls, this study offers recommendations for enhancing the Indian legal framework to ensure more effective deterrence and prosecution of necrophilia. Ultimately, the research underscores the importance of clear, robust legal provisions to address this crime, advocating for legal reforms that balance the need for justice with respect for the sensitivities surrounding the issue.